The features of the linguistic and cultural component in teaching Russian language to Arab students: Особенности лингвокультурологической составляющей в преподавании русского языка арабским учащимся (Journal of the College of Languages (JCL), 2019)
The author addresses the issue of the linguoculturological component in the process of teaching Russian to Arabic students, focuses on the peculiarities of the national character of students. The author also refers to the long-standing ties of Russian and Arab cultures, thus emphasizing the relevance of this aspect for the current state and situation of the Russian language in Arab countries.Автор статьи обращается к вопросу лингвокультурологической составляющей в процессе преподавания русского языка арабским студентам, останавливается на особенностях национального характера обучающихся. Автор основывается на давних связях русской и арабской культур, тем самым подчеркивая актуальность данного аспекта для современного состояния и положения русского языка в арабских странах.